Green Solvents in Carbohydrate Chemistry: From Raw Materials to Fine Chemicals - Farran, Angeles (2015)
In recent decades, there has been an increasing effort to reduce the use of fossil fuels and oil derivatives, to decrease environmental pollution, and to counteract global warming. The use of biomass as raw material is becoming a major alternative to fossil fuels, since it is widely abundant and relatively inexpensive.1 Carbohydrates, that is, cellulose, starch, and sucrose, are important raw materials in the chemical industry because they are produced from biomass that is readily available in large amounts, facilitating their large-scale application. Carbohydrates display important functions in cell physiology and at the nanoscale in cell membranes, as part of glycoconjugates (glycoproteins, glycolipids, and polysaccharides) comprising the glycocalyx. Consequently, carbohydrates have important roles in many biological processes, including bacterial and viral infection, cancer metastasis, apoptosis, neuronal proliferation, and many other crucial intercellular recognition events.